Government Cash Management : Relationship between the Treasury and the Central Bank - Pessoa, Mario (Technical Notes and Manuals; Technical Notes and Manuals ;, 2013)
This technical note and manual (TNM) addresses the following main issues: Interaction between treasury cash management and monetary policy operations within the wider context of the respective economic responsibilities of the ministry of finance and the central bank; Institutional arrangements for an effective relationship between the treasury and the central bank; Contractual arrangements between the treasury and the central bank for the provision of banking and other services. This document will be particularly relevant to developing countries that are reforming cash management operations or contemplating more active cash management; or where there are operational policy differences between the treasury and the central bank.